Endocrinology and diabetes : case studies, questions and commentaries - Ajjan, Ramzi; Gilbey, Stephen (Springer, 2015)
This book assembles a number of real-life clinical cases that illustrate aspects of both diabetes and endocrinology. The cases are described as they may present to the clinician, followed by a series of questions that illustrate the clinical problem and provide background information. All of the clinical vignettes presented have been written by practising physicians and surgeons who encountered these patients in their day-to-day practice. Some represent common presentations of relatively rare conditions, whilst others describe uncommon presentations of more familiar disorders. Endocrinology and Diabetes: Case Studies, Questions and Commentaries will appeal to both trainees in diabetes and endocrinology and more experienced practitioners alike, providing an alternative approach to cover a wide variety of clinical scenarios.